Penggunaan Continous Glucose Monitoring pada Pasien DM Tipe 2 dengan Insulin Dosis Tinggi - Hardigaloeh, Amanda Trixie; Tahapary, Dicky; Yunir, Em; Juli Edi Tarigan, Tri (UI Scholars Hub, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high risk of complications, requiring optimal glycemic control. This case report aims to describe the use of continuous glucose monitoring (CGM) in the evaluation of a patient with T2DM and obesity whose glycemic levels remained uncontrolled despite high-dose insulin therapy. A 58-year-old woman with an 18-year history of T2DM presented to the Endocrinology Clinic of Cipto Mangunkusumo Hospital with uncontrolled blood glucose accompanied by classic diabetic symptoms. CGM revealed that the majority of glucose levels were within the time above range (TAR) at 83% without hypoglycemia, while the time in range (TIR) was only 17%. Contributing factors included a high-carbohydrate diet, limited physical activity, and technical difficulties with insulin injection. Interventions consisted of dietary re-education, gradual physical activity, optimization of injection technique, and insulin dose adjustment. CGM provided a comprehensive glycemic profile and helped identify non-pharmacological factors hindering glycemic control. This case highlights the role of CGM as an essential tool for individualized therapy in patients with T2DM requiring high-dose insulin.